Foreign languages as a prerequisite of a company’s competitiveness on a global market - Cherednichenko, Galina (My University, 2015)
International markets demand multilingual communication strategies which often have to be tailor-made to the requirements of a company. The target must be to reach clients as efficiently and effectively as possible. Міжнародні ринки вимагають багатомовних комунікаційних стратегій, які часто повинні бути зроблені спеціально для вимог компанії. Международные рынки требуют многоязычных коммуникационных стратегий, которые часто должны быть сделаны специально для требований компании.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; communication strategies; комунікаційні стратегії; коммуникационные стратегии; foreign language; иностранный язык; іноземна мова